Peningkatan Hasil Belajar Sosiologi Dengan Model Pembelajaran Kooperatif Tipe Group Investigasi - Marsida Rasyid (PENSOS : Jurnal Penelitian dan Pengabdian Pendidikan Sosiologi, 2024)
This study aimed to determine whether the Group Investigation Learning Model can improve sociology learning outcomes at IPS SMA Muhammadiyah Lamahala. This type of research was Classroom Action Research (PTK), intended to enhance classroom learning. The subjects of this study were students of class XI IPS 2 SMA Muhammadiyah Lamahala, who had a total of 25 students. The instrument used in this study was a test. The research data was analyzed by using quantitative data analysis. Based on the results of the study, it can be concluded that applying the Group Investigation learning model can improve sociology learning outcomes in class XI IPS 2 SMA Muhammadiyah Lamahala by about in the excellent category; in the first cycle, the number of values was 1.520 with an average of 60.8 increasing in the exceptional category, and in the second cycle, the number of values was 2.100 with an average of 84 rising to in the outstanding category. These results have achieved the success criteria set by the researcher, namely 80% above KKM 75.